MT1-MMP: a potent modifier of pericellular microenvironment. - Itoh, Y; Seiki, M (2006)
Cells are regulated by many different means, and there is more and more evidence emerging that changes in the microenvironment greatly affect cell function. MT1-MMP is a type I transmembrane proteinase which participates in pericellular proteolysis of extracellular matrix (ECM) macromolecules. The enzyme is cellular collagenase essential for skeletal development, cancer invasion, growth, and angiogenesis. MT1-MMP promotes cell invasion and motility by pericellular ECM degradation, shedding of CD44 and syndecan1, and by activating ERK. Thus MT1-MMP is one of the factors that influence the cellular microenvironment and thereby affect cell-signaling pathways and eventually alters cellular behavior. As a proteinase, MT1-MMP is regulated by inhibitors, but it also requires formation of a homo-oligomer complex, localization to migration front of the cells, and internalization to become a "functionally active" cell function modifier. Developing new means to inhibit "functional activity" of MT1-MMP may be a new direction to establish treatments for the diseases that MT1-MMP mediates such as cancer and rheumatoid arthritis.